A Systematic Review on Current Research Trends on Student-Centered Pedagogies in English as a Foreign Language (EFL) - Thapa, Deepak (Journal of Educational Research and Innovation, 2024)
Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA is a research method that involves systematically collecting, evaluating, and synthesizing all relevant studies on a specific topic using pre-defined criteria. Following PRISMA guideline, this article examines the current trends and research focus of the researchers on student-centered teaching strategies in English Language Teaching (ELT) from 2020 to 2024. It investigates four main themes: active learning strategies, student engagement in EFL classrooms, participatory teaching and learning, and task-based teaching and learning (TBLT). The findings reveal that task-based teaching and learning as the most extensively researched theme, indicating a notable interest in its effectiveness for enhancing language proficiency among EFL learners. Similarly, there was relatively lesser researches on participatory teaching and learning method compared to TBLT in EFL contexts during the designated period. Furthermore, while active learning strategies and student engagement in EFL classrooms were acknowledged, they did not receive as much research focus as task-based approaches. This study contributes to discussions on effective teaching practices in EFL education by highlighting the distribution of research attention across different student-centered teaching themes. The findings offer valuable guidance for policymakers, educators, and researchers to develop teaching strategies prioritizing active learning and students’ engagement strategies, ultimately leading to improvements in language education and more fulfilling learning experiences for EFL learners.